Structural and room-temperature ferromagnetic properties of pure and Ni-doped TiO2 nanotubes - Patel S.K.S.; Jena P.; Gajbhiye N.S. (My University, 2025)
Diluted magnetic semiconductor based on Ni-doped TiO2 has been synthesized by hydrothermal process and effect of Ni doping on structure, morphology and magnetic studies were investigated. X-ray Rietveld analysis confirmed that all the samples were TiO2 anatase structure without having any impurity phase. The lattice parameter and cell volume increased in Ni-doped TiO2 nanotubes. TEM micrograph reveals clearly the formation of TiO2 nanotubes with diameter of ~8 nm. Magnetic properties studies were carried out by using vibrating sample magnetometer at room temperature and ferromagnetism was observed in both pure and Ni-doped TiO2 nanotubes. The bound magnetic polarons formed by Ni ions and the oxygen vacancy may be responsible for the increased magnetic moment in Ni-doped TiO2 nanotubes. These findings provide a better understanding for the mechanisms of Ni doped TiO2 nanotubes ferromagnetism at room temperature. © 2019 Published by Elsevier Ltd.